2019
DOI: 10.3892/mmr.2019.9917
|View full text |Cite
|
Sign up to set email alerts
|

miR‑155 mediates inflammatory injury of hippocampal neuronal cells via the activation of microglia

Abstract: MicroRNA (miR)-155 has a crucial role in various cellular functions, including differentiation of hematopoietic cells, immunization, inflammation and cardiovascular diseases. The present study aimed to investigate the roles and mechanisms of miR-155 in treatment-resistant depression (TRD). A Cell Counting Kit-8 assay and flow cytometry were performed to assess the cell viability and apoptosis of microglial cells, respectively. Western blotting and reverse transcription-quantitative polymerase chain reaction as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…Although the expression of these miRNAs is known from macrophages, their investigation in microglia is still in its beginning. In the case of miR-155, its proinflammatory role in the microglia has been confirmed [ 118 , 119 , 120 , 121 ]. It was also concluded to favor M1 polarization in microglia, and its suppression was associated with polarization to M2 [ 121 ].…”
Section: Melatonin and Micrornas: Relevance To Microgliamentioning
confidence: 99%
“…Although the expression of these miRNAs is known from macrophages, their investigation in microglia is still in its beginning. In the case of miR-155, its proinflammatory role in the microglia has been confirmed [ 118 , 119 , 120 , 121 ]. It was also concluded to favor M1 polarization in microglia, and its suppression was associated with polarization to M2 [ 121 ].…”
Section: Melatonin and Micrornas: Relevance To Microgliamentioning
confidence: 99%
“…The study conducted on mice cell lines revealed a possible role of miR-155 in the context of treatment-resistant depression. miR-155 down-regulated SOCS1, leading to the activation of microglia that contributes to inflammatory injury of hippocampal neurons [ 114 ]. In contrast, the correlation analysis of miR-155 expression in RR-MS patients (in the remission phase) with the Beck Depression Index (BDI) scale and with Montreal Cognitive Assessment (MoCA) values did not reveal to be statistically significant [ 74 ].…”
Section: Mir-155 and Neuropsychiatric Symptomsmentioning
confidence: 99%
“…Elevations in miR-155 are evident in COVID-19 high-risk, pre-existent conditions, including obesity [ 84 ], type II diabetes [ 85 ], hypertension and CVDs [ 86 ], and most human cancers [ 87 ]. Raised miR-155 levels promotes inflammatory cytokine production in macrophages and microglia, in association with a decrease in sirtuin-1 [ 88 ], linking increased miR-155 to a heightened and prolonged ‘cytokine storm’, including from a primed elevation of miR-155 in high-risk conditions. Preclinical data show the raised miR-155 levels in immune cells to accelerate ageing and decrease longevity via an increase in aerobic glycolysis and associated induction of pro-inflammatory processes [ 89 ].…”
Section: Ahr and Wider Covid-19 Pathophysiologymentioning
confidence: 99%